Modified silicon-carbon negative electrode material and preparation method and application thereof

By coating polymers on the surface and inside of the silicon carbon material with vapor deposition, the problem of insufficient cyclic stability and rate performance is solved, and higher water dispersion and electrochemical performance are achieved. It is suitable for the negative electrode of lithium-ion batteries. Material.

CN119181785AActive Publication Date: 2024-12-24SHINGHWA ADVANCED MATERIAL TECH (MEISHAN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411121100.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-24
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The current vapor-deposited silicon-carbon material has insufficient cycling stability and rate performance in lithium-ion batteries, resulting in insufficient long cycle stability and poor rate performance in practical applications.

Method used

By coating polymers on the surface of the carbon framework of silicon carbon and vapor-phase silicon particles, especially lithiated unsaturated monomers such as lithium polyacrylate, the water dispersion and cycle stability of the material are improved and lithium ion conduction is reduced. impedance, thereby improving the rate performance of the material.

Benefits of technology

The water dispersion, cycle stability and rate performance of the modified silicon carbon anode material is significantly improved, the cycle life of the material is extended and the electrochemical performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181785A_ABST
    Figure CN119181785A_ABST
Patent Text Reader

Abstract

The invention discloses a modified silicon-carbon negative electrode material as well as a preparation method and application thereof, and belongs to the technical field of new energy battery materials. The modified silicon-carbon negative electrode material provided by the invention comprises vapor deposition silicon-carbon, wherein the vapor deposition silicon-carbon comprises a carbon skeleton and vapor silicon; the carbon skeleton has a pore structure, and the deposition position of the vapor phase silicon comprises the pore structure; the arrangement position of the polymer comprises the inner surface and the outer surface of the carbon skeleton and the surface of the gas-phase silicon; a monomer of the polymer is a lithiated unsaturated monomer. The modified silicon-carbon negative electrode material provided by the invention has good cycling stability, rate capability and water dispersibility. The invention also discloses a preparation method and application of the modified silicon-carbon negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery materials, and in particular to a modified silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] Faced with the continuous consumption of fossil energy and the growing demand for sustainable energy, there is an urgent need to develop low-cost, environmentally friendly, and high-performance energy conversion and storage technologies. Lithium-ion batteries have become one of the most promising energy storage technologies due to their high energy density, superior cycle stability, and no environmental pollution or memory effect. At present, the growing electric vehicle market and grid energy storage field are driving rechargeable batteries to develop towards higher energy density and power density. Silicon anodes have a high theoretical capacity (3579mAh / g), a suitable lithiation potential (0.4V vs Li + / Li), good environmental compatibility and high abundance, etc., and has attracted widespread attention. It is considered to be the most promising candidate material for the negative electrode of the next generation of lithium-ion batteries. However, the large volume expansion of silicon (>300%) during the lithiation process has caused a series of problems, which seriously hindered the application of silicon: the huge volume expansion causes the silicon particles to pulverize and break after multiple cycles, resulting in the interruption of electron and ion transmission; at the same time, the volume expansion of silicon during lithiation will promote the growth of irreversible solid electrolytes, and it will continue to fall off during repeated lithiation, continuously consuming electrolytes and causing the loss of active lithium. In summary, due to the problems caused by the volume expansion of silicon, silicon-based lithium-ion batteries have low initial coulombic efficiency (ICE) and poor cycle performance, which cannot meet the needs of industrial applications.

[0003] In recent years, a composite silicon negative electrode with silicon deposited on a carbon skeleton, namely vapor-deposited silicon carbon, has begun to attract attention. Vapor-deposited silicon carbon is a process in which silane gas is introduced into a porous carbon shell at a certain high temperature to undergo a chemical decomposition reaction, thereby obtaining a silicon-carbon composite material in which silicon nanoparticles are dispersed in the porous carbon, which has the characteristics of a micron / nano composite structure. Due to its special structure, vapor-deposited silicon carbon has a high first-cycle discharge specific capacity of up to 2000mAh / g, and its first-cycle coulomb efficiency is higher than that of other silicon-carbon composite materials, generally higher than 90%. However, the volume expansion of the nano-silicon particles in the porous carbon still exists during the cycle, and the stress caused by the huge volume change can easily break the porous carbon skeleton, leading to material failure. Therefore, vapor deposited silicon carbon faces the problem of insufficient long-cycle stability in practical applications. At the same time, due to its microstructural characteristics, the rate performance of vapor deposited silicon carbon negative electrode deposited with carbon skeleton has not yet met the needs of actual industrial applications. Currently, the most commonly used method in the industry is to use vapor deposition to coat a layer of inorganic carbon layer on the surface to stabilize the structural stability of the material during the cycle and improve the rate performance. However, this has limited improvement on the performance of vapor deposited silicon carbon negative electrode.

[0004] In summary, the vapor deposited silicon carbon currently produced has problems such as poor long-cycle stability, poor rate performance, and poor water dispersibility. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a modified silicon-carbon negative electrode material, which can effectively improve the cycle stability, rate performance and water dispersibility of vapor-deposited silicon-carbon.

[0006] The present invention also provides a method for preparing the modified silicon-carbon negative electrode material.

[0007] The present invention also provides the application of the modified silicon-carbon negative electrode material.

[0008] According to an embodiment of the first aspect of the present invention, a modified silicon-carbon negative electrode material is provided, wherein the modified silicon-carbon negative electrode material comprises:

[0009] Vapor-deposited silicon carbon, the vapor-deposited silicon carbon comprises a carbon skeleton and vapor-phase silicon; the carbon skeleton has a pore structure, and the deposition position of the vapor-phase silicon includes the pore structure;

[0010] A polymer, wherein the polymer is disposed on the inner and outer surfaces of the carbon skeleton and the surface of the gas-phase silicon;

[0011] The monomer of the polymer is a lithium-treated unsaturated monomer;

[0012] The unsaturated monomer includes at least one of an acrylate monomer and an acrylate ester monomer.

[0013] The modified silicon-carbon negative electrode material according to the embodiment of the present invention has at least the following beneficial effects:

[0014] The monomer of the polymer is a lithium-treated unsaturated monomer, that is, the polymer is essentially lithium polyacrylate or its derivatives, which have good hydrophilic properties; since the polymer wraps the surface of the vapor-deposited silicon carbon, the obtained modified silicon-carbon negative electrode material has good hydrophilicity and water dispersibility, which can ensure the uniformity and storage stability of the aqueous negative electrode slurry prepared later; and the obtained modified silicon-carbon negative electrode material is compatible with the new silicon negative electrode binder system.

[0015] The polymer exists in the inner and outer surfaces of the carbon skeleton and the surface of the gas-phase silicon; this improves the contact between the carbon skeleton and the nano gas-phase silicon particles, reduces the stress caused by the expansion of the gas-phase silicon particles during the cycle, thereby reducing the stress borne by the carbon skeleton, and ensures the structural integrity of the carbon skeleton from a mechanical level to prevent it from breaking, thereby improving the cycle stability of the modified silicon-carbon negative electrode material obtained; secondly, the polymer also acts as an artificial SEI film to a certain extent, thereby further modifying the performance of the SEI film formed during the cycle. The combination of the two prevents the SEI film from being repeatedly broken and forming a vicious cycle during the charge and discharge process, and promotes the formation of a stable surface, that is, the cycle stability of the modified silicon-carbon negative electrode material is improved from a chemical level.

[0016] The polymer used in the present invention effectively lowers the energy barrier of lithium ion conduction and reduces the impedance; thereby improving the rate performance of the obtained modified silicon-carbon negative electrode material to a certain extent.

[0017] In summary, due to the synergistic effect between vapor-deposited silicon carbon and polymer, the present invention significantly improves the water dispersibility, cycle stability and rate performance of the modified silicon-carbon negative electrode material.

[0018] According to some embodiments of the present invention, the particle size of the gas phase silicon is 1-100 nm.

[0019] According to some embodiments of the present invention, the carbon content of the vapor-deposited silicon carbon is 30% to 60%, for example, about 40%, 45%, 50% or about 55%.

[0020] According to some embodiments of the present invention, the pore structure of the carbon skeleton includes macropores (pore diameter > 50nm), mesopores (pore diameter 2-50nm) and micropores (pore diameter < 2nm). The pore volume of the micropores accounts for 80-90% of the pore volume of the pore structure. The pore volume of the macropores accounts for ≤5% of the pore volume of the pore structure.

[0021] According to some embodiments of the present invention, the acrylate monomers include acrylic acid and its derivatives (referred to as acrylic monomers).

[0022] According to some embodiments of the present invention, the acrylate monomers include acrylates and their derivatives (referred to as acrylate monomers).

[0023] According to some embodiments of the present invention, the D50 of the vapor-deposited silicon carbon is 4-10 μm, for example, about 5 μm, 6 μm, 7 μm, 8 μm or about 9 μm.

[0024] According to some embodiments of the present invention, the specific surface area of ​​the vapor deposited silicon carbon is 1 to 15 m 2 / g. For example, it can be about 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 10m 2 / g or about 12m 2 / g.

[0025] According to some embodiments of the present invention, the tap density of the vapor deposited silicon carbon is 0.6 to 1.4 g / cm 3 For example, it can be about 0.8 g / cm 3 , 0.9g / cm 3 , or about 1.0 g / cm 3 .

[0026] According to some embodiments of the present invention, the first cycle discharge specific capacity of the vapor deposited silicon carbon at 0.1C and 1.5V is 1600-2000mAh / g, for example, about 1700mAh / g, 1800mAh / g or about 1900mAh / g.

[0027] According to some embodiments of the present invention, the first cycle coulombic efficiency of the vapor-deposited silicon carbon at 0.1C and 0.8V is 90-95%, for example, about 91%, 92%, 93% or about 94%.

[0028] According to some embodiments of the present invention, the first cycle discharge specific capacity of the vapor deposited silicon carbon at 0.1C and 0.8V is 1400-1600 mAh / g, for example, about 1500 mAh / g or about 1550 mAh / g.

[0029] According to some embodiments of the present invention, the first cycle coulombic efficiency of the vapor-deposited silicon carbon at 0.1C and 0.8V is 80% to 85%, for example, about 81%, 82%, 83% or about 84%.

[0030] According to some embodiments of the present invention, the mass ratio of the polymer to the vapor deposited silicon carbon is 0.5 to 3.5:10, for example, about 0.8:10, 1:10, 1.2:10, 1.5:10, 1.8:10, 2:10, 2.2:10, 2.5:10 or about 3:10.

[0031] According to an embodiment of the second aspect of the present invention, a method for preparing the modified silicon-carbon negative electrode material is provided, and the preparation method comprises the following steps:

[0032] S1. The unsaturated monomer is subjected to lithium treatment to obtain a modified monomer;

[0033] mixing the modified monomer, vapor deposited silicon carbon and a surfactant;

[0034] S2. The mixture obtained in step S1 and an initiator are mixed and reacted.

[0035] The mechanism of the preparation method is as follows:

[0036] In the mixing in step S1, the modified monomer is adsorbed on the surface of the vapor-deposited silicon carbon, including the inner and outer surfaces of the carbon skeleton and the surface of the vapor-phase silicon particles, through the adsorption effect of the surfactant; the surfactant increases the water dispersibility of the vapor-deposited silicon carbon, thereby increasing the distribution uniformity of the modified monomer on the vapor-deposited silicon carbon.

[0037] In the mixing reaction in step S2, the initiator triggers the in-situ polymerization reaction of the adsorbed and positioned modified monomer.

[0038] Since the preparation method adopts all the technical solutions of the modified silicon-carbon negative electrode material of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0039] Furthermore, the preparation method adopts an in-situ polymerization method to form the polymer, and the modified monomer easily diffuses into the internal pore structure of the carbon skeleton and the surface of the gas phase silicon particles; thus, the setting position of the polymer includes the inner and outer surfaces of the carbon skeleton and the surface of the gas phase silicon. Among them, the polymer on the surface of the gas phase silicon can effectively relieve the stress caused by the volume expansion of the gas phase silicon, and the polymer on the surface of the carbon skeleton can relieve the expansion stress of the gas phase deposited silicon carbon, protecting the carbon skeleton from breaking during the cycle and causing electrode failure. Therefore, the modified silicon-carbon negative electrode material obtained by coating and modifying the gas phase deposited silicon carbon effectively improves the contact interface between the carbon skeleton and the gas phase silicon particles, and at the same time improves the contact interface between the overall particles and the electrolyte. During the cycle, it not only reduces unnecessary side reactions between the electrolyte and the modified silicon-carbon negative electrode material, but also reduces the stress caused by the expansion of the gas phase silicon particles to the carbon skeleton, and comprehensively improves the cycle stability of the modified silicon-carbon negative electrode material from the two aspects of mechanical stability and chemical stability.

[0040] Furthermore, the present invention forms the polymer by in-situ polymerization, whereby the distribution state of the polymer is a uniform and dense coating layer; compared with the traditional point coating, it is more conducive to relieving stress and acting as an artificial SEI.

[0041] The preparation method adopted by the invention is simple, the reaction conditions are mild and the operation process is simple.

[0042] According to some embodiments of the present invention, in step S1, the lithiation treatment method includes reacting the unsaturated monomer and a lithium source in a solvent.

[0043] According to some embodiments of the present invention, the molar ratio of the unsaturated monomer to the lithium source is 1:0.8-1.2, for example, about 1:0.9, 1:0.95, 1:1.05 or about 1:1.1.

[0044] According to some embodiments of the present invention, the pH of the mixture obtained by the lithiation treatment is 6.5 to 8.5. For example, it can be about 7.0, 7.5 or about 8.0. Generally, a specific ratio of unsaturated monomer and lithium source will inevitably result in a specific pH. If it is not within the above range, a trace amount of lithium source can be added as a pH regulator. The amount added as a pH regulator is very small and can be ignored when calculating the molar ratio of the materials.

[0045] According to some embodiments of the present invention, in step S1, the unsaturated monomer includes at least one of methacrylic acid (CAS: 79-41-4), acrylic acid (CAS: 79-10-7), butenedioic acid (CAS: 110-17-8), methyl acrylate (CAS: 96-33-3), butyl acrylate (CAS: 141-32-2), ethyl acrylate (CAS: 140-88-5), methyl 2-methacrylate (CAS: 80-62-6), ethyl 2-methacrylate (CAS: 97-63-2) and vinyl acetate (CAS: 108-05-4). More specifically:

[0046] The olefinic monomer includes at least one of methacrylic acid, acrylic acid and butenedioic acid;

[0047] The acrylate monomer includes at least one of methyl acrylate, butyl acrylate, ethyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate and vinyl acetate.

[0048] According to some embodiments of the present invention, the lithium source includes at least one of lithium carbonate, lithium hydroxide and lithium nitrate.

[0049] According to some embodiments of the present invention, in step S1, the mass ratio of the unsaturated monomer to the vapor deposited silicon carbon is 0.5 to 3.5:10, for example, about 0.8:10, 1:10, 1.2:10, 1.5:10, 1.8:10, 2:10, 2.2:10, 2.5:10 or about 3:10.

[0050] According to some embodiments of the present invention, in step S1, the source of the vapor deposited silicon carbon is purchased commercially.

[0051] According to some embodiments of the present invention, in step S1, the preparation method of vapor-deposited silicon carbon comprises the following steps:

[0052] D1. pyrolyzing the polymer material to obtain the carbon skeleton;

[0053] D2. Introducing silane gas into the carbon skeleton, and converting the silane gas into the gas-phase silicon using a wet pyrolysis method.

[0054] Since the raw material used for preparation is gaseous silane, it can be fully distributed in the pore structure of the carbon skeleton, so the generated gaseous silicon is also evenly distributed in the pore structure of the carbon skeleton; the obtained gas-phase deposited silicon carbon presents a micron / nano structure as a whole. During the electrochemical reaction, the gas-phase silicon particles undergo a lithiation / delithiation process in the pore structure of the carbon skeleton. The carbon skeleton, as a carrier of the gas-phase silicon particles, bears the stress caused by the volume expansion of the gas-phase silicon particles during the cycle. This method can achieve molecular-scale control of the prepared nanomaterials, and the particle morphology is good. At the same time, the gas-phase deposited silicon carbon produced by deposition has uniform components and a dense structure.

[0055] According to some embodiments of the present invention, in step S1, the surfactant includes at least one of hexadecyltrimethylammonium chloride (CAS: 112-02-7), dodecyldimethylbenzylammonium chloride (CAS: 139-07-1), octadecyltrimethylammonium chloride (CAS: 112-03-8), sodium dodecylsulfonate (CAS: 2386-53-0), dodecyltrimethylammonium bromide (CAS: 1119-94-4) and polydiallyldimethylammonium chloride (CAS: 26062-79-3).

[0056] According to some embodiments of the present invention, in step S1, when the surfactant is selected from polydiallyldimethylammonium chloride, the molecular weight of the surfactant is 400,000 to 500,000, for example, about 450,000.

[0057] According to some embodiments of the present invention, in step S1, the mass percentage of the surfactant to the vapor-deposited silicon carbon is 100-200%, for example, about 120%, 140%, 150% or about 160%.

[0058] In actual production, the surfactant is used in the form of an aqueous solution. Specifically, the mass concentration of the aqueous solution is 30-40%, for example, about 35%.

[0059] According to some embodiments of the present invention, step S1 comprises the following steps:

[0060] S1a. The unsaturated monomer and the lithium source are reacted in a solvent; obtaining a mixture A comprising the modified monomer;

[0061] Preliminarily mixing the vapor deposited silicon carbon and the surfactant to obtain a mixture B;

[0062] S1b. Mix the mixture A and the mixture B.

[0063] According to some embodiments of the present invention, in step S1a, the solvent includes water.

[0064] According to some embodiments of the present invention, the mass volume ratio of the vapor-deposited silicon carbon to the solvent is 1 g:10-30 mL, for example, about 1 g:15 mL, 1 g:20 mL or about 1 g:25 mL.

[0065] According to some embodiments of the present invention, in step S1b, the mixing further comprises adding ethanol, wherein the amount of ethanol added is 0.5-1.5% of the volume of the solvent in step S1a, for example, about 1%, thereby further improving the mutual dispersibility between the mixture A and the mixture B.

[0066] According to some embodiments of the present invention, in step S1b, the mixing temperature is 30-50°C, for example, about 40°C.

[0067] According to some embodiments of the present invention, in step S1b, the mixing time is 20 to 60 minutes, for example, about 30 minutes, 40 minutes or about 50 minutes.

[0068] Unlike traditional silicon-based materials, such as silicon-oxygen materials or traditional silicon-carbon materials, the vapor-deposited silicon-carbon used in the present invention is more difficult to disperse in water, and thus it is more difficult to uniformly adsorb the modified monomer in the solvent water. In the preparation method provided by the present invention, the mixing temperature is increased to a certain extent, which promotes the uniformity of adsorption of the modified monomer on the surface of the vapor-deposited silicon-carbon.

[0069] According to some embodiments of the present invention, in step S1, the pH of the obtained mixture is 6 to 9. For example, it can be about 6.5, 7, 7.5 or about 8.

[0070] According to some embodiments of the present invention, in step S2, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, ammonium persulfate, potassium persulfate and sodium persulfate.

[0071] According to some embodiments of the present invention, the mass percentage of the initiator to the unsaturated monomer is 0.1-5%, for example, about 0.5%, 1%, 2%, 3% or about 4%.

[0072] According to some embodiments of the present invention, in step S2, the temperature of the mixing reaction is 40-100°C, for example, about 50°C or about 80°C.

[0073] According to some embodiments of the present invention, in step S2, the duration of the mixing reaction is 1 to 6 hours, for example, about 2 hours or about 4 hours.

[0074] Since the adsorption between the vapor-deposited silicon carbon and the modified monomer is difficult, and it is even more difficult to form a uniform and continuous coating in an aqueous solvent, organic solvents are mostly used in traditional technologies; in the preparation method provided by the present invention, in order to avoid the problem of uneven distribution of the polymer, in addition to adding a small amount of surfactant, the temperature and duration of the mixing reaction in step S2 are appropriately increased, thereby promoting the smooth progress of the in-situ polymerization reaction.

[0075] According to some embodiments of the present invention, step S2 comprises the following steps:

[0076] S2a. preparing an aqueous solution of the initiator;

[0077] S2b: adding the aqueous solution of the initiator to the mixture obtained in step S1.

[0078] According to some embodiments of the present invention, in step S2a, in the aqueous solution, the mass volume ratio of the initiator to the solvent water is 1 mg: 0.5-5 mL, for example, about 1 mg: 0.8 mL, 1 mg: 1 mL, 1 mg: 2 mL, 1 mg: 3 mL or about 1 mg: 4 mL.

[0079] According to some embodiments of the present invention, the preparation method further comprises solid-liquid separation, washing and drying after step S2.

[0080] The method of solid-liquid separation includes centrifugation.

[0081] The washing method includes water washing.

[0082] The drying temperature is 50-80°C; for example, it can be about 60°C or about 70°C.

[0083] The drying time is 6 to 18 hours; for example, it can be about 8 hours, 10 hours, 12 hours, 14 hours or about 16 hours.

[0084] The drying method includes vacuum drying.

[0085] According to an embodiment of the third aspect of the present invention, a lithium-ion battery is provided, wherein the raw materials for preparing the lithium-ion battery include the modified silicon-carbon negative electrode material.

[0086] Since the lithium-ion battery adopts all the technical solutions of the modified silicon-carbon negative electrode material of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0087] According to some embodiments of the present invention, the lithium-ion battery includes at least one of a soft-pack battery, a square-shell battery, a cylindrical battery, a button battery, and an irregular battery.

[0088] According to some embodiments of the present invention, the lithium-ion battery includes at least one of a liquid battery, a semi-solid battery and an all-solid battery.

[0089] According to some embodiments of the present invention, based on the type of solvent in the electrolyte, the lithium-ion battery includes at least one of an aqueous battery and an organic battery.

[0090] According to some embodiments of the present invention, the lithium-ion battery includes a positive electrode and a negative electrode; the raw material for preparing the negative electrode includes the modified silicon-carbon negative electrode material.

[0091] The raw materials for preparing the positive electrode include positive electrode active materials.

[0092] The type of the positive electrode active material is not strictly limited and can be selected according to commercial availability or compatibility in actual production. It should be noted that the modified silicon-carbon negative electrode material provided by the present invention is compatible with all commonly used lithium-ion battery positive electrode active materials in the commercial field at the current stage.

[0093] According to an embodiment of the fourth aspect of the present invention, there is provided an application of the lithium-ion battery in the field of power batteries, energy storage batteries and 3C small household appliances.

[0094] Since the application adopts all the technical solutions of the lithium-ion battery of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0095] According to some embodiments of the present invention, the power battery field includes at least one of electric vehicles and electric motorcycles.

[0096] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0097] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0098] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0099] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0100] Figure 1 It is a schematic diagram of the structure of the modified silicon-carbon negative electrode material prepared in an embodiment of the present invention.

[0101] Figure 2 This is the infrared spectrum of the modified silicon-carbon negative electrode material obtained in Example 1 of the present invention.

[0102] Figure 3 This is the infrared spectrum of vapor deposited silicon carbon A.

[0103] Figure 4 This is a comparison chart of the cycle performance of the modified silicon-carbon negative electrode materials obtained in Examples 1 to 3 of the present invention and the vapor-deposited silicon-carbon A at 0.8 A / g;

[0104] Figure 5 This is a comparison chart of the cycle performance of the modified silicon-carbon negative electrode material obtained in Examples 4 to 5 of the present invention and the vapor-deposited silicon-carbon A at 0.8 A / g;

[0105] Figure 6 This is a comparison chart of the cycle performance of the modified silicon-carbon negative electrode material obtained in Examples 6 to 7 of the present invention and the vapor-deposited silicon-carbon B at 0.8 A / g;

[0106] Figure 7 Comparison of the cycle performance of the modified silicon-carbon negative electrode materials obtained in Examples 6 to 7 of the present invention and vapor-deposited silicon-carbon B at 1.2 A / g;

[0107] Figure 8 Electrochemical impedance diagrams of the modified silicon-carbon negative electrode materials obtained in Examples 6 to 7 of the present invention and vapor-deposited silicon carbon B.

[0108] Reference numerals:

[0109] Carbon skeleton 110 , fumed silicon 120 , polymer 200 , and lithium ions 300 . DETAILED DESCRIPTION

[0110] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0111] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0112] Example 1

[0113] In this example, a modified silicon-carbon negative electrode material was prepared, and the specific steps were as follows:

[0114] S1. Synthetic modified monomer:

[0115] Acrylic acid and a lithium source (Li2CO3) were uniformly mixed in a 200 mL aqueous solution at a molar ratio of 1:1.1, and the pH was controlled at 7.2 to obtain a mixture A including a modified monomer, wherein the mass of the acrylic acid was 0.5 g;

[0116] Prepare mixture B:

[0117] 10 g of vapor-deposited silicon carbon (parameters see vapor-deposited silicon carbon A in Table 1) was mixed with 15 g (based on solid mass) of polydiallyldimethylammonium chloride (molecular weight 450,000, purity = 35 wt % aqueous solution).

[0118] Mixed adsorption:

[0119] Mixture B was added to mixture A, and 2 mL of anhydrous ethanol was added, and stirred at 40° C. for 0.5 h to obtain a uniformly dispersed mixed system. The pH of the obtained mixed system was about 7.5.

[0120] S2. Dissolve 0.005 g of ammonium persulfate in 20 mL of deionized water, and add the resulting aqueous solution of ammonium persulfate to the mixed system obtained in step S1 in four portions, dropping about 5 mL every half an hour.

[0121] After the addition was completed, the mixture was reacted at 40 °C for 2 h;

[0122] S3. The mixture obtained in step S2 was centrifuged, and the obtained solid was washed three times with deionized water, moved into a vacuum drying oven and dried at 50° C. for 12 h to obtain a modified silicon-carbon negative electrode material.

[0123] The structure of the modified silicon-carbon negative electrode material obtained is shown in FIG. Figure 1 As shown, it specifically includes:

[0124] Vapor-deposited silicon carbon, the vapor-deposited silicon carbon includes a carbon skeleton 110 and vapor-phase silicon 120, the carbon skeleton 110 contains a pore structure, and the vapor-phase silicon 120 is located inside the pore structure;

[0125] The polymer 200 is disposed on the inner and outer surfaces of the carbon skeleton 110 and the surface of the gas-phase silicon 120 .

[0126] During the use of the modified silicon-carbon negative electrode material obtained in this example, the lithium ions 300 pass through the carbon skeleton 110 and the polymer 200 and finally react with the gas-phase silicon 120 .

[0127] Example 2

[0128] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 1 in that:

[0129] In step S1, the mass of acrylic acid is 1 g, and the molar ratio of acrylic acid to lithium source is maintained at 1:1.1 (the molar ratio remains unchanged, and the corresponding pH remains unchanged, and the same applies to other embodiments).

[0130] Example 3

[0131] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 1 in that:

[0132] In step S1, the mass of acrylic acid is 2 g, and the molar ratio of acrylic acid to lithium source is maintained at 1:1.1.

[0133] Example 4

[0134] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 1 in that:

[0135] In step S1, the mass of acrylic acid is kept unchanged, and the amount of lithium source is adjusted so that the molar ratio of acrylic acid to lithium source is 1:0.8.

[0136] Correspondingly, the pH of the mixture A obtained in step S1 is 6.5.

[0137] In step S1, the pH of the mixed system after the mixture A and the mixture B are mixed is 6.9.

[0138] Example 5

[0139] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 1 in that:

[0140] In step S1, the mass of acrylic acid is 1 g, and the amount of lithium source is adjusted so that the molar ratio of acrylic acid to lithium source is 1:0.8.

[0141] Correspondingly, the pH of the mixture A obtained in step S1 is 6.5.

[0142] In step S1, the pH of the mixed system after the mixture A and the mixture B are mixed is 6.9.

[0143] Example 6

[0144] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 1 in that:

[0145] (1) In step S1, the mass of acrylic acid is kept constant, and the amount of lithium source is adjusted so that the molar ratio of acrylic acid to lithium source is 1:0.8. Correspondingly, the pH of the mixture A obtained in step S1 is 6.5.

[0146] In step S1, the pH of the mixed system after the mixture A and the mixture B are mixed is 6.9.

[0147] (2) In step S1, the types of vapor-deposited silicon carbon used are different, and the parameters are detailed in Table 1 for vapor-deposited silicon carbon B.

[0148] (3) In step S1, the temperature of mixed adsorption is 60°C.

[0149] (4) In step S2, the mass of the initiator is 0.025 g.

[0150] (5) In step S2, the reaction temperature is 60°C.

[0151] Example 7

[0152] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 6 in that:

[0153] In step S1, the lithium source used is lithium hydroxide. The molar ratio of acrylic acid to the lithium source is kept unchanged, and the amount of acrylic acid used is adjusted to 1.5 g.

[0154] Correspondingly, the pH of the mixture A obtained in step S1 is 7.2;

[0155] In step S1, the pH of the mixed system after the mixture A and the mixture B are mixed is 7.5.

[0156] Table 1 Parameters of vapor-deposited silicon carbon used in the examples

[0157]

[0158] In Table 1, vapor deposited silicon carbon A was purchased from Shida Shenghua New Materials Group Co., Ltd. with the item number SH-S01; vapor deposited silicon carbon B was purchased from Shida Shenghua New Materials Group Co., Ltd. with the item number SH-S02.

[0159] According to the information provided by the merchant, the carbon skeleton used in vapor-deposited silicon carbon A and vapor-deposited silicon carbon B has a BET size of approximately 1633 m2 / g; the micropore volume is about 0.66cm 3 / g, accounting for 89%; the mesopore volume is about 0.07cm 3 / g, accounting for 9.8%; the macropore volume is about 0.005cm 3 / g, accounting for 0.7%. Since the pore structure of the carbon skeleton has a certain limiting effect on the particle size of the gas phase silicon particles, it can be seen that in the modified silicon-carbon negative electrode material provided by the invention, the particle size of the gas phase silicon particles is mainly ≤2nm, and some are distributed between 2 and 50nm.

[0160] Comparative Example 1

[0161] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 1 in that:

[0162] In step S1, acrylic acid is replaced by a mixture of acrylic acid, acrylamide and hexafluorobutyl methacrylate in equal amounts, wherein the mass ratio of acrylic acid:acrylamide:hexafluorobutyl methacrylate is 6:3:1.

[0163] Comparative Example 2

[0164] This example prepares a modified silicon-carbon negative electrode material, which differs from Example 1 in that:

[0165] In step S1, the preparation step of the mixture B and the mixed adsorption step are not included;

[0166] In step S2, after the mixture A and the aqueous solution of ammonium persulfate are directly mixed and reacted, the resulting reactant is mixed with the mixture B and mixed adsorption is performed.

[0167] In this example, the amount of raw materials used in the preparation is the same as that in Example 1.

[0168] Application Example 1

[0169] This example provides a button-type lithium-ion battery. Specifically, the button-type battery includes a negative electrode (working electrode), a lithium metal sheet (counter electrode), a separator disposed between the working electrode and the counter electrode; an electrolyte that soaks the working electrode, the counter electrode and the separator; and a CR2032-type button-type battery case that wraps and contains all of the above components.

[0170] The preparation process of the working electrode is as follows: the active material (modified silicon-carbon negative electrode material provided in the embodiment, and vapor-deposited silicon-carbon A to B), conductive carbon black, single-walled carbon nanotube slurry, binder (CMC), binder (SBR), according to the mass ratio of 91:4.85:0.15:1.5:2.5, are mixed and stirred for 8 hours to obtain a slurry; the slurry is coated on a copper foil, and the active material loading is 1.5 to 2 mg / cm 2After vacuum drying at 60°C for 12 h, it was cut into discs with a diameter of 12 mm using a cutting machine to obtain the negative electrode.

[0171] The electrolyte is composed of lithium salt, solvent and additives; the lithium salt is LiPF6 with a concentration of 1M; the solvent is 1:1 (w) ethylene carbonate (EC) and diethyl carbonate (DEC); the additives are 6wt% (of the electrolyte) of fluoroethylene carbonate (FEC) and 2wt% (of the electrolyte) of ethylene carbonate (VC).

[0172] The button cell was assembled in a glove box isolated from water and oxygen.

[0173] Test Case

[0174] In the first aspect of this example, the infrared spectra of the modified silicon-carbon negative electrode material obtained in Example 1 and the vapor-deposited silicon-carbon A were tested. The results showed that after being coated with lithium polyacrylate, the characteristic peak of lithium polyacrylate appeared on the surface of Example 1. In the standard spectrum, the carboxyl group COOH is at 1700 cm -1 There is a characteristic infrared peak at , which is caused by the stretching vibration of C1 / 4O in the carboxyl group; when Li + Replace H + (COOLi), due to the homogenization of C1 / 4O and CO in the carboxyl group, 1700cm -1 The peak at 1560 cm-1 will disappear, and the peak at 1560 cm-1 will disappear due to the change of dipole moment with the formation of salt. -1 A new peak appears at 1563cm -1 A peak was observed at 1700 cm -1 No peak was observed at + It has completely replaced the H in the carboxyl group + In addition, the modified silicon-carbon negative electrode material obtained in Example 1 has a peak at 842 cm -1 The nearby peak is caused by the carbon-carbon chain absorption in polymer compounds, 1438 cm -1 The peak at is caused by the bending vibration of the CH2 alkyl group, which indicates that lithium polyacrylate is successfully combined with vapor-deposited silicon carbon; the detailed results are shown in Figure 2 As shown. As a comparison, the vapor-deposited silicon carbon A does not include characteristic peaks such as COOLi; the results are shown in Figure 3 shown.

[0175] In the second aspect of this example, the long cycle performance of the modified silicon-carbon negative electrode material obtained in the example and the vapor-deposited silicon-carbon A and vapor-deposited silicon-carbon B was tested. The test conditions were:

[0176] The charge and discharge current density in the first cycle is 200 mA / g, and the first coulombic efficiency of the modified silicon-carbon negative electrode material obtained in the embodiment is greater than 90%;

[0177] The charge and discharge current density of the later cycle is 800 mA / g.

[0178] The test voltage range for first efficiency, capacity and cycle is 0.005V-1.5V.

[0179] The results show:

[0180] The modified silicon-carbon negative electrode material obtained in Example 2 has almost no capacity decay after 150 cycles, while Example 1 is slightly worse than Example 2 and better than Example 3; and Examples 1 to 3 are all better than the long cycle results of vapor-deposited silicon carbon A. This shows that when the amount of polymer used is high, it will hinder the conduction of lithium ions to a certain extent. When the amount of polymer used is small, its wrapping effect cannot be fully exerted. The appropriate amount of polymer can alleviate the volume expansion of vapor-phase silicon particles while enhancing conductivity, greatly improving the cycle stability of vapor-deposited silicon carbon at high current density. The comparison results of Examples 1 to 3 and vapor-deposited silicon carbon A are shown in Figure 2. Figure 4 shown.

[0181] Examples 4 to 5 controlled the pH (ratio of acrylic acid and lithium source) to control the composition of the polymer. The lower the pH, the higher the proportion of polyacrylic acid in the coating layer. Compared with vapor-deposited silicon carbon A, the modified silicon-carbon negative electrode materials obtained in Examples 4 to 5 had a capacity retention rate of more than 95% after 100 cycles of 800 mA / g, indicating that enhanced cycle performance can be obtained by reasonably controlling the components of the polymer layer through pH.

[0182] Comparison of the cycle results of the modified silicon-carbon negative electrode materials obtained in Examples 4 to 5 and the vapor-deposited silicon-carbon A Figure 5 shown.

[0183] The long cycle results of the modified silicon-carbon negative electrode materials obtained in Examples 6 and 7 and the vapor-deposited silicon-carbon B show that the capacity of Example 6 is almost unchanged after 150 cycles, but the thicker coated lithium polyacrylate (Example 7) hinders the lithium ion transmission to a certain extent, so the capacity of Example 7 is slightly lower than that of Example 6. The specific test results are as follows: Figure 6 shown.

[0184] The third aspect of this example tests the electrochemical performance of the modified silicon-carbon negative electrode material obtained in Example 6 and the vapor-deposited silicon-carbon B at high current density. The test conditions are:

[0185] The first cycle charge and discharge current density is 150mA / g;

[0186] The subsequent cycles were subjected to long cycle charge and discharge tests at a current density of 1200 mA / g (about 1C); the test voltage range was 0.005V-1.5V.

[0187] The results show that after 280 cycles, the capacity retention rate of Example 6 is 76.3%, and the specific capacity is 706 mAh / g, while the vapor-deposited silicon carbon is only 162 mAh / g. The specific test results are as follows: Figure 7 shown.

[0188] The fourth aspect of this example tests the electrochemical impedance of the silicon-carbon negative electrode material obtained in Examples 6 to 7 and the vapor-deposited silicon carbon B. The test conditions are 1.5V and 0.01Hz to 100000Hz. The results show that the impedance of the modified silicon-carbon negative electrode material obtained in the example is lower than the impedance of the vapor-deposited silicon carbon B, indicating that the coating layer formed by lithium polyacrylate effectively lowers the energy barrier of lithium ion conduction. The specific test results are as follows Figure 8 shown.

[0189] The test results of the above electrochemical properties are summarized in Table 2.

[0190] Table 2 Electrochemical performance results of modified silicon-carbon negative electrode materials obtained in Example and the vapor-deposited silicon-carbon A-B used therein

[0191]

[0192] In summary, the present invention deposits a layer of polymer on the surface and inside of vapor-deposited silicon carbon through a simple and efficient liquid phase reaction. The material of the polymer includes lithium polyacrylate. An appropriate amount of polymer greatly improves the electrochemical performance of the obtained modified silicon carbon negative electrode material, especially the cycle performance under high current density. The present invention provides a simple and effective method for improving the electrochemical performance of vapor-deposited silicon carbon.

[0193] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A modified silicon-carbon negative electrode material, characterized in that: The modified silicon-carbon negative electrode material comprises: Vapor-deposited silicon carbon, the vapor-deposited silicon carbon comprises a carbon skeleton and vapor-phase silicon; the carbon skeleton has a pore structure, and the deposition position of the vapor-phase silicon includes the pore structure; A polymer, wherein the polymer is disposed on the inner and outer surfaces of the carbon skeleton and the surface of the gas-phase silicon; The monomer of the polymer is a lithium-treated unsaturated monomer; The unsaturated monomer includes at least one of an acrylate monomer and an acrylate ester monomer.

2. The modified silicon-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the polymer to the vapor deposited silicon carbon is 0.5 to 3.5:

10.

3. A method for preparing a modified silicon-carbon negative electrode material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1. The unsaturated monomer is subjected to lithium treatment to obtain a modified monomer; mixing the modified monomer, vapor deposited silicon carbon and a surfactant; S2. The mixture obtained in step S1 and an initiator are mixed and reacted.

4. The preparation method according to claim 3, characterized in that: In step S1, the mass ratio of the unsaturated monomer to the vapor deposited silicon carbon is 0.5 to 3.5:10; and / or the unsaturated monomer includes at least one of methacrylic acid, acrylic acid, succinic acid, methyl acrylate, butyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate and vinyl acetate.

5. The preparation method according to claim 3, characterized in that: In step S1, the lithiation treatment method includes mixing the unsaturated monomer and a lithium source in water.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the unsaturated monomer to the lithium source is 1:0.8-1.2; and / or the pH of the mixture obtained by the lithiation treatment is 6.5-8.

5.

7. The preparation method according to claim 5, characterized in that: The lithium source includes at least one of lithium carbonate, lithium hydroxide and lithium nitrate.

8. The preparation method according to claim 3, characterized in that: The mass percentage of the initiator to the unsaturated monomer is 0.1-5%; preferably, in step S2, the temperature of the mixing reaction is 40-100° C.; preferably, in step S2, the duration of the mixing reaction is 1-6 hours.

9. A lithium ion battery, characterized in that: The raw materials for preparing the lithium-ion battery include the modified silicon-carbon negative electrode material as described in claim 1 or 2.

10. Application of the lithium-ion battery according to claim 9 in the fields of power batteries, energy storage batteries and 3C small household appliances.

Citation Information

Patent Citations

  • Silicon carbon composite material and preparation method thereof

    CN105140477A

  • Negative electrode material and preparation method thereof

    CN116072845A

  • Silicon-based negative electrode material and preparation method and application thereof

    CN117766709A

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN118039825A

  • Silicon or silicon alloy, composite active material for lithium secondary battery containing the same, and manufacturing method thereof

    JP2021180124A